Study of AI and Technology As A Substitute for The Presence of A Teacher Learning The Qur'an Hadith In Bond of Knowledge Perspective - Yulianto, Sandi Ferdy; Haya, Farah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
In Society 5.0 Era, the integration of artificial intelligence (AI) and technology has significantly influenced various education. This study conducts a critical study of the potential of AI and technology as a substitute for teacher presence in teaching Al-Qur'an Hadith. This study aims to evaluate the consistency in scientific texts to maintain the authenticity of religious teachings. This research explores the possibility of utilizing AI, in providing interactive guidance for Al-Qur'an Hadith students. The strengths and limitations of AI are analyzed to understand the interpersonal aspects of the relationship between teachers and students. In addition, this study emphasizes the importance of maintaining the religious context inherent in the teachings of the Al-Qur'an and Hadith. The role of AI in analyzing text content and verifying the credibility of information is discussed, while highlighting the importance of human expertise. This study uses a qualitative methodology, including a literature review, and case studies in the form of interviews from educators and scholars. The research findings aim to provide insight into the potential benefits and challenges of integrating AI and technology in the Al-Qur'an Hadith learning environment. In conclusion, this study emphasizes the importance of achieving a harmonious balance between the progress of AI-based education and the preservation of rich scientific traditions in the study of Al-Qur'an Hadith. This research advocates the use of AI as complementary tools under the guidance of knowledgeable human instructors, thus driving an efficient approach to religious education in the dynamic landscape of Society 5.0.